2021
DOI: 10.3389/fmars.2021.675274
|View full text |Cite
|
Sign up to set email alerts
|

Reef Conservation off the Hook: Can Market Interventions Make Coral Reef Fisheries More Sustainable?

Abstract: The overexploitation of coral reef fisheries threatens the persistence of reef ecosystems and the livelihoods and food security of millions of people. Market-based initiatives to increase fisheries sustainability have been widely implemented in industrialized commodity fisheries, but the suitability of these initiatives for coral reef fisheries has not been systematically investigated. Here, we present a typology of market-based interventions and coral reef fisheries sectors and identity promising approaches f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Many of the social drivers we examined are amenable to governance interventions. For example, our results emphasize that conservation strategies which mediate the negative effects of markets are urgently needed 78,89,90 . Additionally, our study sheds light on how strategically placing reserves based on socioeconomic considerations (e.g.…”
Section: Critiques Caveats and Future Directionsmentioning
confidence: 80%
“…Many of the social drivers we examined are amenable to governance interventions. For example, our results emphasize that conservation strategies which mediate the negative effects of markets are urgently needed 78,89,90 . Additionally, our study sheds light on how strategically placing reserves based on socioeconomic considerations (e.g.…”
Section: Critiques Caveats and Future Directionsmentioning
confidence: 80%
“…Certification will require solving traceability and fidelity issues ( 38 ), active governance (e.g., an internationally focused management organization), evidence-based management for those at-risk species highlighted here, industry buy-in, consumer education, and the incentivization of sustainable practices [see ( 21 ) for possible approaches]. Nevertheless, unlike many other blue-food coral fisheries ( 5 ), we have shown that the MAT’s global value provides considerable fiscal leverage for protecting those communities already most at risk from a business-as-usual future. A MAT-positive future is imaginable, but requires substantial investment from all actors to ensure that the MAT becomes a “force-for-good” and paradigm of sustainable coral reef fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…Fishing is the primary driver of diminished coral reef functions ( 1 , 2 ), compromising ecosystem services for millions of people. With an estimated 6 million coral reef fishers globally ( 3 ), reefs provide ~25% of the total fish catch in emergent nations ( 4 ), but as the target organisms are usually low value ( 5 ), the financial leverage of blue food fisheries to support reef conservation and enhance community livelihoods is limited. In contrast, the marine aquarium trade (MAT) targets biodiversity that can retail for hundreds of U.S. dollars per organism ( 6 ).…”
Section: Introductionmentioning
confidence: 99%